Bridging the "green gap" of LEDs: giant light output enhancement and directional control of LEDs via embedded nano-void photonic crystals. Issue 2 (15th December 2015) - Tsai, Yu-Lin; Liu, Che-Yu; Krishnan, Chirenjeevi; Lin, Da-Wei; Chu, You-Chen; Chen, Tzu-Pei; Shen, Tien-Lin; Kao, Tsung-Sheng; Charlton, Martin D. B.; Yu, Peichen; Lin, Chien-Chung; Kuo, Hao-Chung; et al.
Abstract : Giant light output enhancement and directional control of LEDs were demonstrated via highly scattering multi-layer nano-void photonic crystals. Abstract : Green LEDs do not show the same level of performance as their blue and red cousins, greatly hindering the solid-state lighting development, which is the so-called "green gap". In this work, nano-void photonic crystals (NVPCs) were fabricated to embed within the GaN/InGaN green LEDs by using epitaxial lateral overgrowth (ELO) and nano-sphere lithography techniques. The NVPCs act as an efficient scattering back-reflector to outcouple the guided and downward photons, which not only boost the light extraction efficiency of LEDs with an enhancement of 78% but also collimate the view angle of LEDs from 131.5° to 114.0°. This could be because of the highly scattering nature of NVPCs which reduce the interference giving rise to Fabry–Perot resonance. Moreover, due to the threading dislocation suppression and strain relief by the NVPCs, the internal quantum efficiency was increased by 25% and droop behavior was reduced from 37.4% to 25.9%. The enhancement of light output power can be achieved as high as 151% at a driving current of 350 mA. Giant light output enhancement and directional control via NVPCs point the way towards a promising avenue of solid-state lighting.